English Lexical Acquisition Through Mobile Legends Bang Bang: A Game-Mediated Language Learning Perspective - Widya Tarigan; Aseptiana Parmawati; Iman Santoso (PROJECT (Professional Journal of English Education), 2026)
Language serves as a fundamental means of communication and social interaction. Mobile Legends Bang Bang is a popular online game among adolescents worldwide. The implementation of Mobile Legends Bang Bang as an instructional tool was investigated to identify its contribution to improving lexical mastery among tenth grade students at SMAN 1 Parongpong. The research adopted an explanatory sequential mixed method design. Participants consisted of 30 students in class 10 E. Data collection involved tests, observations, questionnaires, and interviews. Quantitative data were examined through descriptive statistics, a normality test, and paired sample t tests in SPSS to identify significant changes in students’ pre test and post test score. Findings revealed notable improvement in students’ performance. The increase in the mean score from 63.83 (pre-test) to 79.67 (post-test) demonstrates an improvement in students vocabulary after being taught using Mobile Legends Bang Bang as an instructional medium. Questionnaire data revealed positive student responses regarding the integration of Mobile Legends Bang Bang into lexical instruction, while observation and interviews highlighted increased engagement and motivation. These findings suggest that incorporating popular mobile games into language instruction can be an effective and enjoyable strategy for enhancing students’ vocabulary acquisition.